Um signo em desenvolvimento: o conceito de self na filosofia de C. S. Peirce no período de 1865 a 1870 - Lovato, Maria Vitória Canesin (2018)
This dissertation intends to investigate the discussions involving the concept of self in the philosophy of the young Charles Sanders Peirce (1834-1914) between 1865 and 1870. Although the thoughts are from his youth years, we will present arguments to show those were years that brought debates of underlying importance for us to understand how and from which theoretical and methodological contexts the theme self emerges. Since 1865, Peirce reasons the relationship between logic and psychology, and argues, explicitly, for a non-psychological position for logic. Within this context, a strong criticism of introspection is born, and it reveals a detachment from the cartesian spirit and the inclination to understand the process of thinking as intuitive or dependable of psychic factors. In general, the criticism of psychologism in logic will demand a revision of the idea of subjectivity and, more specifically, of the self under new philosophical horizons. Therefore, under his then early theory of signs and his social approach to epistemology, Peirce will negate a notion of self characterized by complete individuality and introspection, opening way to a new and positive characterization of subjectivity buoyed by an objective logic, where all knowledge, including of ourselves, proceed in a mediate way and in reference to an outside world. It’s during the years we study in this dissertation that some of the most important – and most commented – characterizations of the self as a sign and of the self as mere negation, if a separate existence is considered, appear. Along this study we will see that, even under the scope if his early logic investigations between 1865 and 1870, Peirce already admitted to a social and opened understanding of the self, giving way to a new approach, one that is broader and sympathetic to less selfish visions